Soil Data Manager - CGIAR Research Program on Water, Land and Ecosystems (2017)
Algorithms ready. R script for internal functionality under publication on CRAN. We are currently programming the web application. The webb application builds on functionality developed by SLU (markdata.se) but is now to be adapted and scaled to Sub-Saharan Africa.